KONSTRIBUSI JABATAN NOTARIS DALAM PERJANJIAN KREDIT BANK (Solusi, 2022)
Article 1 of Law Number 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning the Position of a Notary, states that a notary is a public official who is authorized to make authentic deeds and other authorities. As a public official who is authorized to make authentic deeds and especially in notarial bank credit agreements that provide legal protection for creditors and debtors for strength of evidence and other authorities and to serve the interests of the community. The inhibiting factors for using notary services in the process of granting credit/bank credit agreements are the bank's policy as outlined in the decision letter of the board of directors regarding notary services in the bank credit agreement; the level of risk is credit provided by the bank with guarantees such as movable and immovable objects; the size of the credit value provided by the bank using authentic agreements/notary services and underhand agreements between creditors and debtors are still legalized by a notary.